2017
DOI: 10.1007/s00442-017-4003-4
|View full text |Cite
|
Sign up to set email alerts
|

Tall young females get ahead: size-specific fecundity in wild kangaroos suggests a steep trade-off with growth

Abstract: When resources are limited, organisms face allocation conflicts. Indeterminate growth creates a persistent conflict with reproduction, as growth may enhance future reproduction, but diverts resources from current reproduction. Little is known about allocation trade-offs in mammals with indeterminate growth. We studied growth and reproduction in adult female eastern grey kangaroos (Macropus giganteus), an iteroparous mammal with indeterminate growth. Allocation trajectories varied with age and size: for 4-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…Brown bears in our study areas, like other long-lived species, invest early in rapid growth in structural size, which is completed by 8−14 years of age; subsequent growth in lean mass occurs when available resources allow (Hilderbrand et al 2018). However, there is individual heterogeneity that likely affects lifehistory tradeoffs between early body growth and reproduction, as seen in other species (see Quesnel et al 2018). Our data suggest that larger females more successfully reproduce and recruit offspring into the population.…”
Section: Discussionmentioning
confidence: 65%
“…Brown bears in our study areas, like other long-lived species, invest early in rapid growth in structural size, which is completed by 8−14 years of age; subsequent growth in lean mass occurs when available resources allow (Hilderbrand et al 2018). However, there is individual heterogeneity that likely affects lifehistory tradeoffs between early body growth and reproduction, as seen in other species (see Quesnel et al 2018). Our data suggest that larger females more successfully reproduce and recruit offspring into the population.…”
Section: Discussionmentioning
confidence: 65%
“…Sebens 3 brought more accurate definitions with a detailed description of growth curves which are variations on attenuating or asymptotic growth. Ectothermic vertebrates (fish, amphibians and reptiles) are considered as groups with indeterminate body growth 49 (but see 1016 ), while endotherms (birds and mammals) are determinate growers 4,17 (but see 1821 ). Nevertheless, current literature is pointing to the problematic classification of animal taxa to specific groups according to the available definitions of body growth 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…This shift in nutrient intake, even over a short time as adults, could have reversed the adverse consequences of being on either extreme juvenile diet, as was found by a grasshopper study (Ageneotettix deorum; Joern and Behmer, 1997). Similar to what I observed in my study, other studies also provide evidence that growth and early fecundity can be beneficial to fitness (e.g., in the female eastern grey kangaroo Macropus gigantus; Quesnel et al, 2018).…”
Section: General Conclusionsupporting
confidence: 82%
“…Another study on birds, using the Siberian jay (Perisoreus infaustus), showed that females trade off reproduction and longevity so as not to risk mortality (Griesser et al, 2017). A complex trade-off between age, size, and fecundity exists in female eastern grey kangaroos (Macropus giganteus), in that older females will trade-off small size in favour of reproduction (Quesnel et al, 2018). More recently, a study of Siberian dwarf hamsters (Phodopus sungorus) and water voles (Arvicola amphibious),…”
Section: Trade-offs Between Fitness Conferring Traits Across Speciesmentioning
confidence: 99%